2012
DOI: 10.1007/s10620-012-2424-9
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Cisplatin Exposure Promotes Methylation of the OCT1 Gene in Human Esophageal Cancer Cells

Abstract: This study shows that long-term exposure to cisplatin promotes methylation of the OCT1 gene in human esophageal cancer cells, which in turn results in cisplatin resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…In the case of HCC, this event may be at least partially due to an enhanced methylation and reduced activity of the SLC22A1 promoter . OCT1 down‐regulation has already been associated with chemoresistance in certain types of cancer, for instance, to cisplatin . Moreover, OCT1 expression levels have been suggested to be a useful biomarker to predict the success of imatinib‐based therapy for chronic myeloid leukemia .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of HCC, this event may be at least partially due to an enhanced methylation and reduced activity of the SLC22A1 promoter . OCT1 down‐regulation has already been associated with chemoresistance in certain types of cancer, for instance, to cisplatin . Moreover, OCT1 expression levels have been suggested to be a useful biomarker to predict the success of imatinib‐based therapy for chronic myeloid leukemia .…”
Section: Discussionmentioning
confidence: 99%
“…30 OCT1 down-regulation has already been associated with chemoresistance in certain types of cancer, for instance, to cisplatin. 31 Moreover, OCT1 expression levels have been suggested to be a useful biomarker to predict the success of imatinib-based therapy for chronic myeloid leukemia. 32 The present study suggests that reduced OCT1-mediated sorafenib uptake may be involved in a poorer response to this drug.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, OCT1 is linked to various human tumors. The abnormal expression of OCT1 is associated with a poor patient survival rate and tumor progression [5][6][7]. However, little is known about the roles of OCT1 in colorectal carcinogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…OCT1 promotes the tumor engraftment frequency and the potential of hematopoietic stem cell engraftment in competitive and serial transplants (7). An additional study revealed that methylation of the OCT1 gene in human esophageal cancer cells is induced by long-term cisplatin exposure, resulting in cisplatin resistance (8). The abnormal change of OCT1 is associated with tumor progression and a poor patient survival rate (9).…”
Section: Introductionmentioning
confidence: 99%